Traditional Medicine for Children among Kaluppini Indigenous People in South Sulawesi - Nurbaya Nurbaya; Wahyu Chandra; Pramesthi Widya Hapsari (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
The traditional knowledge about the use of ancestral medicines to cure children was highly valued by the indigenous community and an essential part of their indigenous health system. This study aimed to provide insight into the traditional medication using plant-based medication to children in an indigenous community in South Sulawesi Province. This study was conducted in Kaluppini Village, Enrekang Regency, South Sulawesi. In-depth interviews and focus group discussions were conducted both in Bahasa Indonesia and the local language. Informants were traditional birth attendants and mothers of under-five. This study was carried out from January to June 2018. Data were analyzed using thematic coding. It is found that Kaluppini mothers have traditional knowledge of treatment. They used kinds of plants as traditional remedies to cure their children. This traditional medication named as pembollo’ and pejappi. Pembollo’ are traditional plants intended to cure sick children. Kaluppini people believe that pejappi is a collection of traditional plant that can treat kinds of illnesses among children, including to prevent them from supernatural things. Kaluppini indigenous people practice and believe in their traditional plants to cure their children. Traditional birth attendants play a crucial role in providing these traditional plants. Information provided in this study could be a rational basis for health-related stakeholders to develop programs of health education and promotion for indigenous communities.